(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The Investment decision of investors is subjective considering their dependence on various factors such as socio-demographic variables, risk perception, objectives, and financial information awareness. Behavioral finance molds the traditional definition of risk which implies deviation from actual return with the perception towards the risk which tends to vary from one individual to another. Risk perception plays an important role in determining investment choice. The study attempts to identify the prominent factors having impact on the risk perception of individual investors of Sikkim with the help of Factor Analysis. Primary data consisting of 250 individuals were collected by self-survey method. There are four factors influencing the risk perception namely, Risk Opportunist, Overconfident Risk Bearer, Unrealistic Anticipator, and Cognizant Pursuer. Binary logistic regression further enabled to understand their impact on the investment preference towards the equity shares. The study revealed a significant and positive relationship between risk perception and financial information awareness.